Sex differences in the phenotypic expression of obsessive-compulsive disorder: an exploratory study from Brazil - Torresan, Ricardo Cezar [UNESP]; de Abreu Ramos-Cerqueira, Ana Teresa [UNESP]; de Mathis, Maria Alice; Diniz, Juliana Belo; Ferrao, Ygor Arzeno; Miguel, Euripedes Constantino; Torres, Albina Rodrigues [UNESP] (W B Saunders Co-elsevier Inc, 2009)
Previous studies have shown differences in clinical features of obsessive-compulsive disorder (OCD) between men and women, including mean age at onset of obsessive-compulsive symptoms (OCS), types of OCS, comorbid disorders, course, and prognosis. The aim of this study was to compare male and female Brazilian patients with OCD on several demographic and clinical characteristics. Three hundred thirty Outpatients with OCD (Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition [DSM-IV], criteria) who sought treatment at 3 Brazilian public universities and at 2 private practice clinics in the city of São Paulo were evaluated. The assessment instruments used were the Yale-Brown Obsessive-Compulsive Scale to evaluate OCD severity and symptoms, the Beck Depression and Anxiety Inventories, the Yale Global Tic Severity Scale, and the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Axis I Disorders to assess psychiatric comorbidity.Fifty-five percent of the patients (n = 182) were men who were significantly more likely than women to be single and to present sexual, religious, and symmetry obsessions and mental rituals. They also presented earlier onset of OCS and earlier symptom interference in functioning, and significantly more comorbid tic disorders and posttraumatic stress disorder. Women, besides showing significantly higher mean scores in the Beck Depression and Anxiety Inventories, were more likely to present comorbid simple phobias, eating disorders in general and anorexia in particular, impulse control disorders in general, and compulsive buying and skin picking in particular. No significant differences were observed between sexes concerning family history of OCS or OCD, and global symptoms severity, either in obsession or compulsive subscale. The present study confirms the presence of sex-related differences described in other countries and cultures. The fact that the OCS start earlier and probably have a worse impact in men can eventually lead to more specific and efficacious treatment approaches for these patients. (C) 2009 Elsevier B.V. All rights reserved.